How inclusive leadership catalyze innovative work behaviour: the moderating effect of psychological ownership - Rajandran, Kogulan; Subramaniam, Anusuiya (University of Malaya, 2023)
The aim of the present study was to investigate the impact of inclusive leadership on innovative work behaviour, while considering the role of psychological ownership as a moderator. This researchtopic has received limited attention in the context of university academic research. To achieve this objective, a survey was conducted among 300 faculty of business academics from five Malaysian research universities, aiming to establish a relatively standardized setting. Data analysis was performed using SPSS 26 and SmartPLS version 4 software. The study findings revealed a non-significant relationship between inclusive leadership and innovative work behaviour. However, it was found that psychological ownership significantly moderated the positive relationship between inclusive leadership and innovative work behaviour. These findings providea significant contribution to the existing literature on inclusive leadership, innovative work behaviour, and psychological ownership among academics in universities.